First polarization study of the M87 jet and active galactic nuclei at submillimeter wavelengths with ALMA - Goddi, Ciriaco; Carlos, Douglas F.; Crew, Geoffrey B.; Matthews, Lynn D.; Messias, Hugo; Mus, Alejandro; Marti-Vidal, Ivan; Albentosa-Ruiz, Ezequiel; De Laurentis, Mariafelicia; Liuzzo, Elisabetta; Marchili, Nicola; Rygl, Kazi L. J.; et al. (EDP Sciences, 2026)
Aims. We investigated the polarization and Faraday properties of Messier 87 (M87) and seven other radio-loud active galactic nuclei (AGNs) at lambda 0.87 mm (345 GHz) using the Atacama Large Millimeter/submillimeter Array (ALMA). Our goal was to characterize the linear polarization (LP) fractions, measure Faraday rotation measures (RMs), and examine the magnetic field structures in the emission regions of these AGNs. Methods. We conducted full-polarization observations as part of the ALMA Band 7 very long baseline interferometry (VLBI) commissioning during the April 2021 Event Horizon Telescope (EHT) campaign. We analyzed the LP fractions and RMs to assess the nature of Faraday screens and magnetic fields in the submillimeter emission regions. Results. We find LP fractions between 1% and 17% and RMs exceeding 10(5) rad m(-2), which are 1-2 orders of magnitude higher than typically observed at longer wavelengths (lambda>3 mm). This suggests denser Faraday screens or stronger magnetic fields. Additionally, we present the first submillimeter polarized images of the M87 jet and the observed AGNs, revealing RM gradients and sign reversals in the M87 jet indicative of a kiloparsec-scale helical magnetic field structure. Conclusions. Our results provide essential constraints for calibrating, analyzing, and interpreting VLBI data from the EHT at 345 GHz, representing a critical step toward submillimeter VLBI imaging.